International Migration of Doctors, and Its Impact on Availability of Psychiatrists in Low and Middle Income Countries - Jenkins, Rachel (Public Library of Science, 2010)
BACKGROUND: Migration of health professionals from low and middle income countries to rich countries is a large scale and long-standing phenomenon, which is detrimental to the health systems in the donor countries. We sought to explore the extent of psychiatric migration. METHODS: In our study, we use the respective professional databases in each country to establish the numbers of psychiatrists currently registered in the UK, US, New Zealand, and Australia who originate from other countries. We also estimate the impact of this migration on the psychiatrist population ratios in the donor countries. FINDINGS: We document large numbers of psychiatrists currently registered in the UK, US, New Zealand and Australia originating from India (4687 psychiatrists), Pakistan (1158), Bangladesh (149) , Nigeria (384) , Egypt (484), Sri Lanka (142), Philippines (1593). For some countries of origin, the numbers of psychiatrists currently registered within high-income countries' professional databases are very small (e.g., 5 psychiatrists of Tanzanian origin registered in the 4 high-income countries we studied), but this number is very significant compared to the 15 psychiatrists currently registered in Tanzania). Without such emigration, many countries would have more than double the number of psychiatrists per 100, 000 population (e.g. Bangladesh, Myanmar, Afghanistan, Egypt, Syria, Lebanon); and some countries would have had five to eight times more psychiatrists per 100,000 (e.g. Philippines, Pakistan, Sri Lanka, Liberia, Nigeria and Zambia). CONCLUSIONS: Large numbers of psychiatrists originating from key low and middle income countries are currently registered in the UK, US, New Zealand and Australia, with concomitant impact on the psychiatrist/population ratio n the originating countries. We suggest that creative international policy approaches are needed to ensure the individual migration rights of health professionals do not compromise societal population rights to health, and that there are public and fair agreements between countries within an internationally agreed framework.